Smart Stimuli-Responsive Liposomal Nanohybrid Systems: A Critical Review of Theranostic Behavior in Cancer - Jana K. Alwattar; Amina T. Mneimneh; Kawthar K. Abla; Mohammed M. Mehanna; Ahmed N. Allam (MDPI AG, 2021)
The epoch of nanotechnology has authorized novel investigation strategies in the area of drug delivery. Liposomes are attractive biomimetic nanocarriers characterized by their biocompatibility, high loading capacity, and their ability to reduce encapsulated drug toxicity. Nevertheless, various limitations including physical instability, lack of site specificity, and low targeting abilities have impeded the use of solo liposomes. Metal nanocarriers are emerging moieties that can enhance the therapeutic activity of many drugs with improved release and targeted potential, yet numerous barriers, such as colloidal instability, cellular toxicity, and poor cellular uptake, restrain their applicability in vivo. The empire of nanohybrid systems has shelled to overcome these curbs and to combine the criteria of liposomes and metal nanocarriers for successful theranostic delivery. Metallic moieties can be embedded or functionalized on the liposomal systems. The current review sheds light on different liposomal-metal nanohybrid systems that were designed as cellular bearers for therapeutic agents, delivering them to their targeted terminus to combat one of the most widely recognized diseases, cancer.